EVALUATION OF STUDENTS’ IMAGES OF CITY CENTER: AKSARAY-TURKEY - Funda V. UZUN (European Journal of Geography)
On the basis of field and cameral studies of objects of prehistoric cultural heritage, the authors analyzed the influence of navigation (movement and navigation in geographical space-time) on the processes of biological and over-biological adaptation in anthropogenic (2.62 million years). The article presents some results of the research. It is shown that instrumental astronomical navigation distinguishes human from other biological species. The cold and changeable climate of the anthropogen forced a human to move, to go beyond the limits of the developed landscape, to improve the technologies of navigation in space-time. The first tools of astronomical observations could be sustainable elements of the landscape, created by the energy of nature: mountains, rocks, large rock cracks. The human energy was later added to these objects: man-made additions, artificial objects, graphic signs. The most advanced ancient technology was the shadow of the gnomon of a sundial-calendar (object or own figure). Astronomical signs are abstract in shape (points, lines, circles), but are specific in content (as they perform the function of changing space-time). Continuous use of abstract signs in the life support system could improve the thinking of the ancient human. The navigation concept and new research methods can be applied to solving problems of archeology, anthropology, semiotics, and paleo-linguistics. For example, in explaining the cosmic content of traditional cultures, to clarify the semantics of ancient signs and images, the selection of the invariant of Nostratic languages.